2015
DOI: 10.3171/2014.11.jns14770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exosomes derived from multipluripotent mesenchymal stromal cells on functional recovery and neurovascular plasticity in rats after traumatic brain injury

Abstract: Object Transplanted multipotent mesenchymal stromal cells (MSCs) improve functional recovery in rats after traumatic brain injury (TBI). Here, we test a novel hypothesis that systemic administration of cell-free exosomes generated from MSCs promotes functional recovery and neurovascular remodeling in rats after TBI. Methods Wistar rats were subjected to TBI followed by tail vein injection of 100 μg protein of exosomes derived from MSCs or an equal volume of vehicle phosphate-buffered saline (n = 8/group) 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
479
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(499 citation statements)
references
References 106 publications
15
479
0
5
Order By: Relevance
“…Arslan et al (2013) showed that a single intravenous administration of exosomes was effective in enhancing cardiac function and geometry after myocardial infarction due to bioenergetics re-establishment (increased ATP production), oxidative stress reduction and prosurvival signaling activation (enhanced PI3K/Akt signaling) (Arslan et al, 2013 (Nakamura et al, 2015). In the nervous system, MSC derived exosomes have been evaluated in the treatment of neurological and neurodegenerative diseases; they have been shown to enhance angiogenesis and neurogenesis, reduce inflammation and improve spatial learning and sensorimotor function (Kim et al, 2016;Zhang et al, 2015).…”
Section: Hematopoietic Stem Cell Based Drugsmentioning
confidence: 99%
“…Arslan et al (2013) showed that a single intravenous administration of exosomes was effective in enhancing cardiac function and geometry after myocardial infarction due to bioenergetics re-establishment (increased ATP production), oxidative stress reduction and prosurvival signaling activation (enhanced PI3K/Akt signaling) (Arslan et al, 2013 (Nakamura et al, 2015). In the nervous system, MSC derived exosomes have been evaluated in the treatment of neurological and neurodegenerative diseases; they have been shown to enhance angiogenesis and neurogenesis, reduce inflammation and improve spatial learning and sensorimotor function (Kim et al, 2016;Zhang et al, 2015).…”
Section: Hematopoietic Stem Cell Based Drugsmentioning
confidence: 99%
“…Exosomes play an important role in intercellular communication and are promising therapeutic agents because their complex cargo of proteins and genetic materials has diverse biochemical potential to participate in multiple biochemical and cellular processes, an important attribute in the treatment of complex diseases with multiple secondary injury mechanisms involved [45]. The refinement of MSC therapy from a cell-based therapy to cell-free exosome-based therapy offers several advantages, as it eases the arduous task of preserving cell viability and function, storage, and delivery to patient [175][176][177][178]. Further exploring the mechanisms by which the secretion-based paracrine effect of MSCs participates in neurorestoration and functional recovery following TBI is an outstanding opportunity for research.…”
Section: Neuroprotective and Neurorestorative Processes In The Traumamentioning
confidence: 99%
“…However, previous studies show that only a small proportion of transplanted MSCs actually survive and few MSCs differentiate into neural cells in injured brain tissues. It seems that the predominant mechanisms by which MSCs participate in brain remodeling and functional recovery are likely related to their secretion-based paracrine effect rather than a cell replacement effect [45,[175][176][177][178] ( Figure 2).…”
Section: Neuroprotective and Neurorestorative Processes In The Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrate that small cellularly secreted vesicles called exosomes mediate much of MSCs' tissue healing capabilities [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. MSC derived exosomes are internalized by target cells and transfer proteins, RNA, lipids and metabolites [29].…”
Section: Phenotype Of Mscsmentioning
confidence: 99%